2014
DOI: 10.1080/02687038.2014.975182
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of working memory to language comprehension: differential effect of aphasia type

Abstract: Background: Experimental studies of short-term memory and working memory (WM) in aphasia fail to discriminate cognitive impairments of different aphasia types-nonfluent, Broca-type aphasia and fluent, Wernicke-type aphasia. However, based on the varying fundamental features of these two aphasia syndromes, the potentially different underlying mechanisms of impairment and scant preliminary evidence of varying cognitive deficits, a differential relationship between cognitive function and language processing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 60 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…Executive control abilities play an important role in supporting specific language functions, such as the relationship between updating and sentence comprehension, or inhibition and lexical retrieval (Hussey & Novick, 2012;Ivanova et al, 2015;Jefferies, Patterson, & Ralph, 2008;Novick et al, 2010;Ye & Zhou, 2009). Therefore, it is important to measure executive control using specific and targeted tasks, tapping into each of these subdomains.…”
Section: Are Different Domains Of Executive Control More Vulnerable Imentioning
confidence: 99%
See 1 more Smart Citation
“…Executive control abilities play an important role in supporting specific language functions, such as the relationship between updating and sentence comprehension, or inhibition and lexical retrieval (Hussey & Novick, 2012;Ivanova et al, 2015;Jefferies, Patterson, & Ralph, 2008;Novick et al, 2010;Ye & Zhou, 2009). Therefore, it is important to measure executive control using specific and targeted tasks, tapping into each of these subdomains.…”
Section: Are Different Domains Of Executive Control More Vulnerable Imentioning
confidence: 99%
“…The neural networks that underlie executive control abilities are highly distributed across frontal, parietal and subcortical structures bilaterally (Alvarez & Emory, 2006;Duncan & Owen, 2000;Nee, Wager, & Jonides, 2007;Wager et al, 2005). Consequently, there is both overlap and divergence between the executive control and language networks (Woolgar, Duncan, Manes, & Fedorenko, 2018;Ye & Zhou, 2009) and it is likely that some executive control abilities play an important role in supporting some specific language functions including lexical access, sentence comprehension, and semantic cognition (Hussey & Novick, 2012;Ivanova, Dragoy, Kuptsova, Ulicheva, & Laurinavichyute, 2015;Jefferies & Lambon Ralph, 2006;Novick, Trueswell, & Thompson-Schill, 2010;Pompon, McNeil, Spencer, & Kendall, 2015). As such, the executive control network is vulnerable to lesions associated with aphasia (Keil & Kaszniak, 2002) with previous neuropsychological studies reporting deficits in executive control abilities in acute (El Hachioui et al, 2014;Seniów, Litwin, & Leśniak, 2009) and chronic (Purdy, 2002) aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the degree of aphasia severity predicted impaired performance on supposedly non-verbal tasks such as problem-solving and executive functioning (Baldo, Paulraj, Curran, & Dronkers, 2015). Working memory was found to be related to language abilities, particularly comprehension, in aphasic individuals (Ivanova, Dragoy, Kuptsova, Ulicheva, & Laurinavichyute, 2015; Sung et al, 2009), and Riès and colleagues have shown the effects of cognitive control demands on word selection (Riès, Karzmark, Navarrete, Knight, & Dronkers, 2015). Such new findings strongly suggest that language cannot be studied in isolation, as it has strong connections with other brain networks supporting higher-level cognition.…”
Section: Language Research In the Late 20th Century And Beyondmentioning
confidence: 99%
“…In PWA, numerous researchers have reported limited working memory capacity (e.g., Caspari, Parkinson, LaPointe, & Katz, 1998; Ivanova, Dragoy, Kuptsova, Ulicheva & Laurinavichyute, 2015; Martin, Shelton, & Yaffee, 1994; Tompkins, Bloise, Timko & Baumgaertner, 1994). One study found that the relationship between working memory and comprehension was strong only in nonfluent aphasia, but not in fluent aphasia, suggesting a three-way interaction between comprehension, working memory and fluency (Ivanova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that the relationship between working memory and comprehension was strong only in nonfluent aphasia, but not in fluent aphasia, suggesting a three-way interaction between comprehension, working memory and fluency (Ivanova et al, 2015). As is the case with most PWA research reviewed in this paper, fluency was not measured, but was inferred from aphasia subtype.…”
Section: Introductionmentioning
confidence: 99%